Effect of brand positioning and brand awareness on repurchase intention and consumer satisfaction (study on online marketplace)/ Tasya Amanda and Meta Andriani - Amanda, Tasya; Andriani, Meta
This study was conducted to assess the effect of Brand Positioning, Brand awareness on Consumer Satisfaction and Repurchase Intention in the Online Marketplace. This study uses 100 respondents aged 18-35 years old that already have used the Online Marketplace e-commerce platform and are domiciled in the Jakarta, Bogor, Depok, Tangerang, Bekasi area. This study uses primary quantitative research methods to make the data obtained more accurate. This study uses the PLS-SEM data processing technique and is supported by SmartPLS 3.0 software that uses the outer and inner models. This study's results indicate each variable's effect on the intention to repurchase at Online Marketplace. The results of this study have implications for Online Marketplace to see what factors need to be considered that affect the intention to repurchase at Online Marketplace.